2002
DOI: 10.1044/1059-0889(2002/020)
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss- and Hearing Aid-Related Stigma

Abstract: Impaired hearing and the use of hearing aids are often perceived negatively. Many adults deny hearing loss and reject amplification, in part due to such stigma. Women and men differ in how they age and adjust to impaired hearing, yet little is known specifically about women's perceptions of stigma related to hearing loss and hearing aid use. The purpose of this study was to examine the degree of stigma associated with hearing loss and hearing aid use among women in three age groups (35-45 years, 55-65 years, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(37 citation statements)
references
References 16 publications
0
35
0
2
Order By: Relevance
“…Further, barriers are also associated with psychosocial aspects 21,36. Stigmatization has been frequently mentioned in previous studies2325 and should be taken into account. By focusing on incentives for getting a hearing aid, achieving individual goals, and identifying mental and physical barriers, people with hearing impairments would be encouraged to gain skills that would benefit them in the short and long term.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Further, barriers are also associated with psychosocial aspects 21,36. Stigmatization has been frequently mentioned in previous studies2325 and should be taken into account. By focusing on incentives for getting a hearing aid, achieving individual goals, and identifying mental and physical barriers, people with hearing impairments would be encouraged to gain skills that would benefit them in the short and long term.…”
Section: Discussionmentioning
confidence: 88%
“…A clinical study found some low but significant correlations between attitudes and measured HL 22. Stigmatization is frequently mentioned as a significant factor for having a reserved attitude toward hearing aids 23,24. In the Valby Project, which surveys hearing in elderly people aged ≥80 years who are not provided with hearing aids, 62% of those surveyed reported a wish for a hearing aid to be “invisible”, and 28% expressed that a hearing aid “makes you old” 25.…”
Section: Introduction and Purposementioning
confidence: 99%
“…There is a discussion within the scientific community about whether the M4 recommendation alone is appropriate for capturing presbyacusis, with it being argued that 6,000 and 8,000 Hz should be included in the evaluation 18. There have been different practices:19,20 there are at least two studies that have included the frequencies 6,000 and 8,000 Hz,21,22 but the M4 recommendation with 500, 1,000, 2,000, and 4,000 Hz is the most used.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have found that perceived stigma has an influence on decisionmaking processes that occur during initial acceptance of hearing loss, testing, and use of hearing aids [18]. Additionally, this stigma is not exclusive to men and is perceived by younger women as well [19]. Efforts to reduce the stigma surrounding hearing loss may increase the number of Veterans who return for follow-up visits after the comprehensive evaluation.…”
Section: Discussionmentioning
confidence: 99%